Pengaruh Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), Profitabilitas, dan Sales Growth Terhadap Tax avoidance: Studi pada Perusahaan Manufaktur Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Sylvia Nur Fatimah; Mujiyati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Tax avoidance is an effort mde by taxpayers to reduce the tax burden in a way that does not violate tax laws and regulations. This study aims to analyze the influence of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), profitability, and sales growth on tax avoidance in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange during the 2021-2023 period. By using a quantitative approach and purposive sampling methods. The variables studied include tax avoidance measurement using Cash Effective Tax Rate (CETR), GCG with institutional ownership, audit committee, and independent board of commissioners, CSR measurement, and profitability measured by Return on Assets (ROA), and sales growth. The analysis was carried out through multiple linear regression and hypothesis testing. The results of the study show that the variables of the Board of Independent Commissioners, Profitability, and Sales Growth have an effect on Tax avoidance. Meanwhile, the variables of Institutional Ownership, Audit Committee, CSR have no effect on Tax avoidance.